2018
DOI: 10.1186/s12870-018-1409-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals that tricarboxylic acid cycle-related genes are associated with maize CMS-C fertility restoration

Abstract: BackgroundC-type cytoplasmic male sterility (CMS-C) is one of the three major types of cytoplasmic male sterility (CMS) in maize. Rf4 is a dominant restorer gene for CMS-C and has great value in hybrid maize breeding, but little information concerning its functional mechanism is known.ResultsTo reveal the functional mechanism of Rf4, we developed a pair of maize near-isogenic lines (NILs) for the Rf4 locus, which included a NIL_rf4 male-sterile line and a NIL_Rf4 male fertility-restored line. Genetic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Functional characterization of the WS-induced candidate genes is required to further identify candidate genes controlling waterlogging-tolerant traits. Additionally, recent studies demonstrated that differentially-regulated genes controlling for the traits of interest could be accurately identified using comparative transcriptome RNA-seq analysis of near-isogenic lines (NILs) [66,67]. Clearly, this method could help to narrow down the list of candidate genes responsible for waterlogging tolerance in zombi pea by removing genetic background effects.…”
Section: Discussionmentioning
confidence: 99%
“…Functional characterization of the WS-induced candidate genes is required to further identify candidate genes controlling waterlogging-tolerant traits. Additionally, recent studies demonstrated that differentially-regulated genes controlling for the traits of interest could be accurately identified using comparative transcriptome RNA-seq analysis of near-isogenic lines (NILs) [66,67]. Clearly, this method could help to narrow down the list of candidate genes responsible for waterlogging tolerance in zombi pea by removing genetic background effects.…”
Section: Discussionmentioning
confidence: 99%
“…The expression data of each gene were obtained from three biological replicates, each of which was measured at least three times. In addition, part of the expression data was retrieved from our previous report [67].…”
Section: Methodsmentioning
confidence: 99%
“…The CMS system is an efficient, economical tool for exploitation of heterosis by maize breeders. Although maize CMS‐C has been widely used in hybrid seed production, and extensive research involving segregating population (Kohls et al., 2011; Tang et al., 2001), genomics (Allen et al., 2007), epigenetics (Chen et al., 2016; Li et al., 2017a), transcriptomics (Li et al., 2017b; Liu et al., 2018; Xue et al., 2019), has been conducted, the molecular mechanism of sterility and restoration in CMS‐C maize remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%